Trimer IgG and neutralising antibody response to COVID-19 mRNA vaccination in individuals with sarcoidosis. Issue 1 (3rd January 2023) - Vagts, Christen L.; Chang, Yi-Shin; Ascoli, Christian; Lee, Jessica M.; Huang, Kai; Huang, Yue; Cherian, Ruth A.; Sarup, Nandini; Warpecha, Samantha R.; Edafetanure-Ibeh, Russell; Amin, Md-Ruhul; Sultana, Tasmin; et al.
Background: Individuals with sarcoidosis are at higher risk for infection owing to underlying disease pathogenesis and need for immunosuppressive treatment. Current knowledge as to how subjects with sarcoidosis respond to different forms of vaccination is limited. We examined quantitative and functional antibody response to COVID-19 vaccination in infection-naive subjects with and without sarcoidosis. Methods: Our prospective cohort study recruited 14 subjects with biopsy-proven sarcoidosis and 27 age–sex matched controls who underwent a two-shot series of the BNT162b2 mRNA vaccine at the University of Illinois at Chicago. Baseline, 4-week and 6-month trimer spike protein IgG and neutralising antibody (nAb) titres were assessed. Correlation and multivariate regression analysis was conducted. Results: Sarcoidosis subjects had a significant increase in short-term antibody production to a level comparable to controls; however, IgG titres significantly declined back to baseline levels by 6 months. Corresponding neutralising assays revealed robust nAb titres in sarcoidosis subjects that persisted at 6 months. A significant and strong correlation between IgG and nAb titres across all time points was observed in the control group. However within the sarcoidosis group, a significant but weak correlation between antibody levels was found. Overall, IgG levels were poor predictors of nAb titres at short- or long-term time points. Conclusions: Sarcoidosis subjects exhibit nAb induced by the BNT162b2 mRNA SARS-CoV-2 vaccine at levels comparable to controls that persists at 6 months indicating conferred immunity. Trimer IgG levels are poor predictors of nAb in subjects with sarcoidosis. Studies of further antibody immunoglobulins and subtypes warrant investigation. While subjects with sarcoidosis have a diminished quantitative antibody (anti-trimer) response to the BNT162b2 mRNA #COVID19 vaccine, their functional neutralising antibody response is comparable to controls, indicating conferred immunity https://bit.ly/3TtqUQZ